2017
DOI: 10.1097/icb.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Retinal Arterial Macroaneurysm on the Optic Disk

Abstract: Detection of optic disk macroaneurysms at the time of initial presentation can be difficult because of concurrent overlying hemorrhage, but should nevertheless be kept in the differential when macular hemorrhage in multiple retinal layers is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…ONH RAMs are usually associated with vascular occlusions, 7 anomalous retinal vasculature, 8 abnormal cilioretinal artery, and Sneddon’s syndrome. 9 A case of ONH RAM with secondary rupture leading to multi-layered haemorrhages in the retina was reported by Rahimy et al 10 FA should be done to confirm the diagnosis, although dense haemorrhage can block fluorescence enough to obscure the macroaneurysm. In such cases, the use of indocyanine green angiography allows visualization of the macroaneursym through haemorrhage.…”
Section: Discussionmentioning
confidence: 98%
“…ONH RAMs are usually associated with vascular occlusions, 7 anomalous retinal vasculature, 8 abnormal cilioretinal artery, and Sneddon’s syndrome. 9 A case of ONH RAM with secondary rupture leading to multi-layered haemorrhages in the retina was reported by Rahimy et al 10 FA should be done to confirm the diagnosis, although dense haemorrhage can block fluorescence enough to obscure the macroaneurysm. In such cases, the use of indocyanine green angiography allows visualization of the macroaneursym through haemorrhage.…”
Section: Discussionmentioning
confidence: 98%
“…However, RAMs on the optic disc mostly involute without any intervention and treatment is only required for symptomatic and complicated cases. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 5 None of those cases were associated with the optic disc. Rahimy et al 7 described multimodal imaging findings including SD-OCT of a case of ruptured macroaneurysm on the disc with thrombosis. Nagai et al reported a case of optic disc macroaneurysm treated with posterior subtenon's kenalog injection with pre- and post-treatment SD-OCT images.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to RAMs located outside of optic nerve, branch retinal arteriolar occlusion following rupture of an ONRAM resulting in secondary closure of distal vasculature seems to be a disproportionately common event, having been reported in 5 of 18 reported cases of ONRAMs [ 8 , 10 , 11 , 12 , 17 ]. Subhyaloid or vitreous, but not submacular, hemorrhage following rupture of ONRAMs has been reported in 8 eyes in five publications [ 6 , 7 , 8 , 9 , 18 ]. It cleared spontaneously in 3 eyes [ 6 , 7 , 18 ], while 5 eyes in three publications required vitrectomy [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subhyaloid or vitreous, but not submacular, hemorrhage following rupture of ONRAMs has been reported in 8 eyes in five publications [ 6 , 7 , 8 , 9 , 18 ]. It cleared spontaneously in 3 eyes [ 6 , 7 , 18 ], while 5 eyes in three publications required vitrectomy [ 7 , 8 , 9 ]. Spontaneous involution of ONRAM occurred in each of 8 eyes with vitreous or subhyaloid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%